Physical activity experiences of young people in an area of disadvantage: 'there's nothing there for big kids, like us'. Issue 8 (16th November 2016) - McEvoy, Eileen; MacPhail, Ann; Enright, Eimear
Abstract : Through an examination of the experiences of young people in one disadvantaged area, this paper adds to an emerging body of knowledge focused on what place physical activity occupies in the lives of young people in areas of disadvantage. A total of 40 young people (21 males, 19 females) participated in focus group interviews. The research question explored the forces which enable and constrain the participation of youths in physical activity and the interplay between such forces and how they experience and exercise agency. All focus group interviews were transcribed, coded and thematically analysed. The findings remind us that young people can be seen as positioned within multiple social relations conferred by specific social identities (such as child, friend, brother or sister) and each of these identities influences the ability of youth to exercise agency in choosing whether, where and when to participate in physical activity. Institutional structures also influenced the physical activity habits of young people in this study. It was interesting to note that staying out of trouble was one of the most discussed benefits of physical activity. Young people also recorded feelings of disempowerment through the belief that no significance was attributed to their words and shared thoughts. This sense of constrained agency presents a particular difficulty when we consider that it is only through accessing the voices of young people that those attempting to promote physical activity can ensure that the range of opportunities being created are matched to the preferences of youth.